The Structure of Interrogative Sentences in Langkat Malay: An Analysis of X-Bar Theory - Mellya Miranda Putri; Mulyadi Mulyadi; Gustianingsih Gustianingsih (RETORIKA: Jurnal Ilmu Bahasa, 2024)
This research discussed the structure of interrogative sentences in Langkat Malay. Langkat Malay is one of local language in Indonesia which is still used in Langkat but the Langkat Malay just understand by the old people because this language doesn’t teach to the younger population in Langkat. Beside that the problem of this study is how the structure of interrogative sentences in Langkat Malay. This research is analyzed using X-bar theory. This research was done because of there is question words have function as complemetizer but question words usually as a specifier. This research used a qualitative approach. Data collection was done by observation and interview methods. Data analysis used the Agih method. which is a determining tool that refers to the language or part of the language such as words, syntactic functions, clauses, word syllables, pitch, etc (Sudaryanto, 2015). The presentation of data results is done using formal and informal methods. The results showed that rules are produced in interrogative sentences in Langkat Malay are: 1) C + Spec + I + Comp, 2) Spec + I + Comp, 3) Spec + Comp, and 4) C + Spec + Comp.